Lo indecible: el motivo del libro, texto y relato en la narrativa de Ricardo Piglia - Pluta, Nina (Romanica Silesiana)
The poetics of the para sensation novel written, among others, by Ricardo Piglia, consisting in looking for a lost book is examined by Nina Pluta. The author draws the conclusion that the very narration scheme is a pretext to reflection on the unsaidness which shows the borderline between the language and literature. Keywords: para-thriller; the motif of a book lost; ineffability; boundaries of language; boundaries of literature <br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />